2017
DOI: 10.4103/jfcm.jfcm_5_17
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of Dammam primary health care centers to deal with emergency cases

Abstract: OBJECTIVES:The objective of the study was to assess the availability of human and nonhuman resources for emergency medical services (EMSs) at the primary health care (PHC) level.MATERIALS AND METHODS:A cross-sectional study with mixed research methods (quantitative and qualitative) was carried out in governmental PHC centers in Dammam, Eastern Province of Saudi Arabia, between September 2014 and January 2015. Using systematic random sampling technique, 13 out of 26 PHC centers were included in the study. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Although participants supported the integration of physical therapists within PHC teams; however, the key cited barrier to this integration was the lack of competent PT professionals and adequately equipped facilities. This finding is similar to those identified by Alsaad et al 33) in their study examining the availability of human resources at the PHC centers in Dammam, Saudi Arabia that showed a deficiency in infrastructure and supporting facilities. According to the Saudi Commission for Health Specialties (SCHS) recent report on the reality of the Saudi health workforce over the next 10 years, there are a total of 6,028 licensed physical therapists in Saudi Arabia in 2017.…”
Section: Discussionsupporting
confidence: 90%
“…Although participants supported the integration of physical therapists within PHC teams; however, the key cited barrier to this integration was the lack of competent PT professionals and adequately equipped facilities. This finding is similar to those identified by Alsaad et al 33) in their study examining the availability of human resources at the PHC centers in Dammam, Saudi Arabia that showed a deficiency in infrastructure and supporting facilities. According to the Saudi Commission for Health Specialties (SCHS) recent report on the reality of the Saudi health workforce over the next 10 years, there are a total of 6,028 licensed physical therapists in Saudi Arabia in 2017.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, quite a few studies have reported variety in staff knowledge, training and education regarding preparedness for disaster emergency incidents. [14][15][16]19,21 Thus, the objective of this study is to assess the knowledge, practices, and attitudes regarding disaster and emergency preparedness among ED staff at a tertiary health care hospital.…”
mentioning
confidence: 99%
“…It is estimated that emergency cases constitute approximately 5% of all cases in primary healthcare centers [ 1 ]. The primary care centers may not be adequately equipped for proper management of emergency cases [ 2 ]. Physicians in primary healthcare centers depend largely on their skills in history taking and physical examination to establish a diagnosis considering limited access to other assessment tools [ 3 ].…”
Section: Introductionmentioning
confidence: 99%